KERJA SAMA INDONESIA DAN SWISS MELALUI MUTUAL LEGAL ASSISTANCE IN CRIMINAL MATTERS UNTUK MENGEMBALIKAN ASSET HASIL KORUPSI TAHUN 2019-2022 - Dian Islami (2023)
The rise of corruption cases in Indonesia has made it possible for many corruptors to hide their assets in other countries, including Switzerland. Recovering or returning assets is known as Mutual Legal Assistance (MLA). The purpose of MLA is to collect and exchange information, evidence and testimony that can be used in investigations and criminal proceedings. In 2019, Indonesia and Switzerland agreed to sign an Agreement on Mutual Assistance in Criminal Matters between the Republic of Indonesia and the Swiss on federation (Treaty on Mutual Legal Assistance (MLA) in Criminal Matters. Mutual legal assistance can be requested for purposes such as taking evidence or statements from persons - people, serving judicial documents, conducting searches and seizures, and providing information, evidence, and expert evaluations. This study aims to find out how the MLA agreements that have been made by the governments of Indonesia and Switzerland in implementing the scope contained in article 2 Law NO 5 of 2020 concerning Mutual Assistance Agreements in Criminal Matters between the Republic of Indonesia and the Swiss Confederation. In this study the authors used a qualitative approach and descriptive research type. The author also uses Bilateral Cooperation Theory and International Agreement Theory. Researchers also use the concept of Mutual Legal Assistance to help analyze this problem. The results of this study state that the Cooperation Between Indonesia and Switzerland in the MLA Agreement is not yet fully effective. The assistance requested by Indonesia to Switzerland has not been fully implemented because there are still many obstacles in each case. Starting from differences in the legal system, lack of material resources, lack of evidence obtained to the absence of political will on the part of the Swiss government